The influence of fastener spacing on the slip modulus between cold formed steel and wood sheathing - Loehr, Weston (Kansas State University, 2016)
Composite action is the joint behavior of two elements connected or bonded together. It is a phenomenon that is utilized in several applications throughout engineering. Previous studies have shown that cold formed steel (CFS) sheathed with structural wood panels exhibits a degree of partial composite action behavior. However currently in the design process, CFS and wood sheathing systems are considered separately in a non-composite manner due to the absence of sufficient supporting data. These systems can include the floors, roofs, and walls of a building. In order to determine the level of composite action present, the slip modulus is needed. The slip modulus describes the relationship between the shear force and the displacement exhibited by two elements in a composite system. The scope of this research is to determine the influence of fastener spacing on the slip modulus and provide a foundation of information to fully define the composite action between CFS and wood sheathing.
Keywords: Engineering; Cold-formed steel; Composite action; Slip modulus